Labour Market, Wages and Their Policies in the EU Area - Andrei Dalina (Holistica, 2018)
Interesting and challenging is not exactly that economic thinking is divided between those who admit that labour would be a good negotiated on its specific market segment and those who don’t, but other two-three aspects. The one is that those who do admit it are classic, neoclassic and (interestingly!) Marxian schools. The last thinkers certainly see it as pejorative. Interesting is equally that those who ‘reject labour market concept’ work around the Keynesian thinking school. The author of ‘General Theory…’ rejected the idea that employer and employee could ever be economically equal to each other and that labour could keep any real market supply specific behaviour. Thirdly, Keynes was the first one who pointed to unemployment as a real modern problem, but also interestingly his view on the same unemployment wasn’t satisfactory for our present.